Harvard College Project for Asian and International Relations (HPAIR) [Brochure] - (:unkn) unknown (My University, 2019)
The Harvard College Project for Asian and International Relations (HPAIR) was founded in 1991 to create a forum of exchange for students and young professionals to discuss and learn about the most important economic, political, and social issues facing the Asia-Pacific region. Since 1991, HPAIR has organized 43 conferences in 12 different host countries, touching the lives of more than 10,000 students and young professionals. HPAIR hosts two student-led conferences a year – one on Harvard’s campus and one in the Asia-Pacific. Prospective host cities in Asia must undergo an intensive, six month bidding process; this year’s Asia Conference will be held in Nur-Sultan, HPAIR’s first conference in Central Asia.
https://hpair.org/
Keywords: Harvard College Project for Asian and International Relations; politic issues; social issues; economic issues